Analysis of Language Errors in The Writing Aspect of Observation Report Texts Students at MTS Pancasila - Susanty Siregar, Susi; Rahmat Kartolo; Sutikno; Ahmad Laut Hasibuan; Julpirman Siregar (PT Inovasi Pratama Internasional, 2026)
This study aims to analyze the language errors contained in the observation report texts (LHO) of class VII A students of MTS Pancasila Tanjung Beringin and identify the causal factors to improve the quality of writing learning. This study uses a qualitative approach with descriptive methods and document analysis study types. The research data are in the form of 24 observation report texts written by class VII A students. The study found a total of 847 language errors from 24 essays (an average of 35.3 errors per essay). The distribution of errors based on category is: (1) punctuation errors 287 errors (33.9%); (2) sentence structure errors 180 errors (21.3%); (3) spelling errors 156 errors (18.4%); (4) diction errors 154 errors (18.2%); and (5) cohesion-coherence errors 70 errors (8.3%). The most dominant type of error was the use of commas (156 errors, 18.4% of the total), followed by subject-predicate mismatch (67 errors, 7.9%), and inappropriate word choice (89 errors, 10.5%). Analysis of the causes of errors revealed that errors were mainly caused by: (1) pedagogical factors (40%) - minimal emphasis on learning punctuation and sentence structure; (2) psycholinguistic factors (30%) - limited working memory and lack of attention when writing; (3) intralingual error (20%) - imperfect mastery of Indonesian language rules; and (4) interlingual error and sociolinguistic factors (10%) - the influence of everyday language and regional languages. Grade VII A students still experienced a high level of language errors in writing observation report texts, especially in the aspects of punctuation and sentence structure. The results can serve as a basis for teachers to design more targeted remediation programs and improve the overall quality of writing instruction